FGF‐2 promotes osteocyte differentiation through increased E11/podoplanin expression. Issue 7 (23rd January 2018) - Ikpegbu, Ekele; Basta, Lena; Clements, Dylan N.; Fleming, Robert; Vincent, Tonia L.; Buttle, David J.; Pitsillides, Andrew A.; Staines, Katherine A.; Farquharson, Colin
Abstract : E11/podoplanin is critical in the early stages of osteoblast‐to‐osteocyte transitions (osteocytogenesis), however, the upstream events which regulate E11 expression are unknown. The aim of this study was to examine the effects of FGF‐2 on E11‐mediated osteocytogenesis and to reveal the nature of the underlying signaling pathways regulating this process. Exposure of MC3T3 osteoblast‐like cells and murine primary osteoblasts to FGF‐2 (10 ng/ml) increased E11 mRNA and protein expression ( p  < 0.05) after 4, 6, and 24 hr. FGF‐2 induced changes in E11 expression were also accompanied by significant ( p  < 0.01) increases in Phex and Dmp1 (osteocyte markers) expression and decreases in Col1a1, Postn, Bglap, and Alpl (osteoblast markers) expression. Immunofluorescent microscopy revealed that FGF‐2 stimulated E11 expression, facilitated the translocation of E11 toward the cell membrane, and subsequently promoted the formation of osteocyte‐like dendrites in MC3T3 and primary osteoblasts. siRNA knock down of E11 expression achieved >70% reduction of basal E11 mRNA expression ( p  < 0.05) and effectively abrogated FGF‐2‐related changes in E11 expression and dendrite formation. FGF‐2 strongly activated the ERK signaling pathway in osteoblast‐like cells but inhibition of this pathway did not block the ability of FGF‐2 to enhance E11 expression or to promote acquisition of the osteocyte phenotype. The results of this study highlight a novel mechanism by which FGF‐2 can regulate osteoblast differentiation and osteocyte formation. Specifically, the data suggests that FGF‐2 promotes osteocytogenesis through increased E11 expression and further studies will identify if this regulatory pathway is essential for bone development and maintenance in health and disease. Abstract : E11/podoplanin is critical in the early stages of osteoblast‐to‐osteocyte transitions (osteocytogenesis), however, the upstream events which regulate E11 expression are unknown. The results of this study highlight a novel mechanism by which FGF‐2 promotes E11 expression and subsequently promotes osteocytogenesis. This will advance understanding on the full repertoire of FGF‐2 function in bone, which may provide insights into the etiology of skeletal disorders such as osteoporosis and osteoarthritis.